Cross-cultural adaptation and translation of oral health educational materials into the Kaingang indigenous language - Pereira, Renato; del Carmen Perez Puello, Sthefanie; Baldani, Márcia Helena; Schuller, Annemarie Adriana; da Luz Rosário de Sousa, Maria; Jesus Batista, Marília; Fraga, Letícia; Ferreira Silva Júnior, Manoelito (Guará Journal, 2023)
The objective of this study was to describe the cross-cultural adaptation and translation of oral health educational materials into the Kaingang indigenous language. The study considered three stages: 1) conceptual equivalence; 2) item and semantic equivalence; 3) back-translation. Of the eight materials used, seven were adapted: 1) healthy and/or restored teeth; 2) periodontal disease; 3) dentures; 4) removable prostheses; 5) dentures and removable prostheses; 6) orthodontic appliances and 7) spaces for missing teeth; and one was excluded: 8) fixed prostheses and implants. During the adaptation process, it was necessary to remove recommendations with difficult semantics, include recommendations and adjust terms to facilitate understanding, and maintain a term in Portuguese (“postinho de saúde” and “flúor”). The materials are the first to consider the cultural and social aspects of an indigenous population in Brazil.
Keywords: oral health education; health of indigenous people; translating